Pengaruh Tindakan Mirror Therapy Terhadap Kekuatan Otot pada Pasien Stroke di Unit Rehabilitasi RSPAD Gatot Soebroto - Siti Nur Fadillah; Wilda Fauzia; Imam Subiyanto (Journal of Innovative and Creativity, 2026)
Stroke is a neurological condition that often causes motor function disorders in the form of decreased muscle strength, especially in the extremities, which impacts the patient's ability to perform daily activities. Rehabilitation efforts are needed to maximize the recovery of motor function, one of which is through non-pharmacological treatment interventions such as mirror therapy. This therapy works by providing visual stimulation through mirrors to activate the motor areas of the brain and support neuroplasticity mechanisms. To determine the effect of mirror therapy on muscle strength in stroke patients in the Rehabilitation Unit of RSPAD Gatot Soebroto. This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. Data collection was conducted from early December to the end of December 2025. The study sample consisted of stroke patients treated at the Stroke Unit of Gatot Soebroto Army Hospital and met the inclusion criteria using a purposive sampling technique. Muscle strength was measured before and after mirror therapy intervention using Manual Muscle Testing (MMT). Showed an increase in muscle strength after mirror therapy. The statistical test results showed a p-value <0.05, so it can be concluded that there was a significant difference between muscle strength before and after mirror therapy intervention.